FDI and their participation in global value chains: An analysis based on East Asia - Mbena Jacques Yana (Studia Ekonomiczne i Regionalne)
East Asia, particularly China, Japan, and South Korea has experienced rapid economic growth in recent decades, partly through active participation in global value chains (GVCs). Foreign direct investment (FDI) has played a crucial role in this process, enabling the transfer of technology and skills and access to international markets. This paper aims to empirically analyse the effects of FDI on GVCs in East Asian countries over the last two decades.